Atividade repelente e larvicida de Xylopia laevigata, X. frutescens (Annonaceae) e Lippia pedunculosa (Verbenaceae) sobre mosquitos Aedes aegypti (Diptera-Culicidae) - Nascimento, Ana Mércia Dias (2014)
Dengue is an important arboviral disease transmitted to humans through the bite of female mosquito Aedes aegypti. As there is no vaccine available, the control of disease occurs, mainly, by the reduction of mosquito population and personal protection to prevent contact between hosts and vectors. Given the increasing process of chemical resistance to insecticides, natural products emerge as safer alternatives for integrated control of endemic diseases. The aim of this work was to evaluate the larvicidal and repellent activities of essentials oils extracted from Xylopia laevigata, Xylopia frutescens and Lippia pedunculosa and of their majority compounds, piperitenone oxide and r-limonene. The larvicidal activity was investigated by exposure of third instar larvae to different concentrations of essentials oils. After 24 hours of exposition, larvae showing lack of mobility or inability to move to water s surface were considered as dead. The repellency effect was based on the suppression of mosquitoes landing on human skin. Essentials oils were diluted in ethanol and applied directly over the volunteer s skin. For each essential oil were performed 12 tests, in which oils concentrations ranged from 0.1 to 10%. The essential oil of L. pedunculosa and its major volatile compounds were shown to be toxic for Ae. aegypti larvae, with CL50 lower than 60 ppm. In the other hand, plants of Xylopia genus just proved to be toxic to Ae. aegypti when in concentrations higher than 1000 ppm. This fact make their use in large-scale unfeasible. All plants tested provided some degree of protection against mosquitoes landing. However only the essential oil of L. pedunculosa and piperitenone oxide provided 100 % of protection against mosquito landings when tested in concentrations lower than 1%. Although its performamnce against dengue mosquitoes, the essential oil of L. pedunculosa shows toxicity the human skin. Therefore, further studies are required to get formulations which are able to provide longer time protection.